A fuzzy-QFD approach to balanced scorecard using an analytic network process. (1st January 2013) - Tavana, Madjid; Mousavi, Nasim; Golara, Sina
The balanced scorecard (BSC) is a strategic management method that links performance measurement to vision and strategies using a multidimensional set of financial and non-financial performance metrics. Although several studies have combined the BSC method with multi-criteria decision analysis methodologies, most of the research efforts do not consider the essentials of strategic and performance management in a systematic and holistic framework capable of handling imprecision and vagueness. The purpose of this study is to present a novel approach for structuring and prioritising the performance measures in the BSC method. The contribution of the proposed approach is fivefold: 1) we use the quality function deployment (QFD) technique to create a linkage between the BSC perspectives; 2) we use the analytic network process (ANP) technique to consider the interactions between the performance measures in each BSC perspective; 3) we integrate the QFD and the ANP techniques to help decision makers understand the relations between the performance measures in different perspectives and the correlations among the performance measures in the same perspective; 4) we handle the vagueness and ambiguity in decision makers' judgements with the fuzzy set theory; 5) we present a case study to demonstrate the applicability of the proposed approach and exhibit the efficacy of the procedures.